'Accuser of Brothers': A Polish Anti-Demonological Tract and its Self-Defeating Rhetoric. Issue 3 (1st September 2020) - Ostling, Michael
ABSTRACT: Polish historiography has celebrated the Czarownica powołana [The Denounced Witch] without studying it very closely, treating its author as a heroic, skeptical, enlightened voice crying out against the witch-trials of Poland-Lithuania. But the anonymous author was probably a Jesuit priest, and indubitably was a fervent proponent for Counter-Reformation. Although the author does condemn the cruel treatment of accused witches, his critique is aimed to return witch-trials to ecclesiastical courts – a step toward reasserting Catholic jurisdiction over all spiritual matters, including Protestant 'heresy.' It is probable that the very strategy which made the Denounced Witch so popular among certain factions of the Catholic church hierarchy rendered it anathema to noble or burgher reformers interested in ameliorating the plight of accused witches.